Analisis Miskonsepsi Siswa SDN 1 Padokan Menggunakan Tes Diagnostik Two-Tier Pada Materi Wujud Zat Dan Perubahannya - Edwin Airlangga; Wahyu Kurniawati (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2026)
Science learning in elementary school requires strong conceptual understanding so that students can relate everyday phenomena to scientific explanations. However, inaccurate prior knowledge often leads to misconceptions, particularly in the topic of states of matter and their changes. This study aimed to identify and analyze the level of misconceptions among fourth-grade students of SDN 1 Padokan using a two-tier diagnostic test. The research employed a quantitative descriptive approach involving 56 students, consisting of 28 students from class IV A and 28 students from class IV B. The instrument used was a 25-item two-tier diagnostic test, and the data were analyzed using percentage calculations to determine the level of misconceptions. The results revealed that the percentage of misconceptions was 55% (moderate category) in the subtopic of types of matter, 64% (high category) in the characteristics of matter, and 66% (high category) in changes in states of matter. These findings indicate that many students still experience difficulties in understanding the properties of matter and the processes of phase changes, especially in linking macroscopic phenomena with particle-level concepts. Therefore, more active and contextual learning strategies, along with continuous use of diagnostic assessments, are necessary to reduce students’ misconceptions.